GOSWAMI TULSIDAS JI'S ETERNAL WORK RAMCHARITMANAS: SCIENTIFIC DEPICTION - Mishra, Om (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Ramcharitmanas is a great book which is considered to be the best epic of the world. Goswami Tulsidas ji has presented the ideal character of Ram in this epic. The story of this epic is full of historicity. In the Bhakti period of Hindi literature, the Tulsi era can be considered to be from 1532-1623 AD. Humayun (1530-1538, Cultural Dimensions of Tulsi Literature, page number 76-77) lived in this era. It was prevalent during the reign of Sher Shah (1530-1555) and Jahangir (1605-1628).1 Along with this, this book also describes religion, ethics, philosophy and science. Goswami Tulsidas ji, while describing historical events in Ramcharitmanas, made this book of high class by describing the devotion of Ram. In such a situation, this book proves to be of very high class. In this book, views have been expressed on the contemporary form of science. Goswami Tulsidas ji has considered the origin of science from renunciation. Without science, the feeling of equality cannot be achieved in life. He has described science as different from knowledge and described it as high class and well-organized knowledge:- ‘Artha Dharam Kaamadik Chari. Kahab Gyan Bigyaan Bichari.’ ‘Brahmacharjbrat Sanjam Nana. Dheeraj Dharam Gyan Bigyaana.’2